Targeting expression to megakaryocytes and platelets by lineage‐specific lentiviral vectors. (13th February 2017) - Latorre‐Rey, L. J.; Wintterle, S.; Dütting, S.; Kohlscheen, S.; Abel, T.; Schenk, F.; Wingert, S.; Rieger, M. A.; Nieswandt, B.; Heinz, N.; Modlich, U.
Abstract : Essentials Platelet phenotypes can be modified by lentiviral transduction of hematopoietic stem cells. Megakaryocyte‐specific lentiviral vectors were tested in vitro and in vivo for restricted expression. The glycoprotein 6 vector expressed almost exclusively in megakaryocytes. The platelet factor 4 vector was the strongest but with activity in hematopoietic stem cells. Summary: Background: Lentiviral transduction and transplantation of hematopoietic stem cells (HSCs) can be utilized to modify the phenotype of megakaryocytes and platelets. As the genetic modification in HSCs is transmitted onto all hematopoietic progenies, transgene expression from the vector should be restricted to megakaryocytes to avoid un‐physiologic effects by ectopic transgene expression. This can be achieved by lentiviral vectors that control expression by lineage‐specific promoters. Methods: In this study, we introduced promoters of megakaryocyte/platelet‐specific genes, namely human glycoprotein 6 (hGP6) and hGP9, into third generation lentiviral vectors and analyzed their functionality in vitro and in vivo in bone marrow transplantation assays. Their specificity and efficiency of expression was compared with lentiviral vectors utilizing the promoters of murine platelet factor 4 (mPf4) and hGP1BA, both with strong activity in megakaryocytes (MKs) used in earlier studies, and the ubiquitously expressing phosphoglycerate kinase (hPGK) and spleen focus forming virus (SFFV) enhancer/promoters. Results: Expression from the mPf4 vector in MKs and platelets was the strongest similar to expression from the viral SFFV promoter, however, the mPf4 vector, also exhibited considerable off‐target expression in hematopoietic stem and progenitor cells. In contrast, the newly generated hGP6 vector was highly specific to megakaryocytes and platelets. The specificity was also retained when reducing the promoter size to 350 bp, making it a valuable new tool for lentiviral expression in MKs/platelets. Conclusion: MK‐specific vectors express preferentially in the megakaryocyte lineage. These vectors can be applied to develop murine models to study megakaryocyte and platelet function, or for gene therapy targeting proteins to platelets.